2018
DOI: 10.3389/fmed.2018.00035
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Anti-Cyclic Citrullinated Peptide Positive At-Risk Individuals Do Not Differ from Those Patients with Early Inflammatory Arthritis

Abstract: ObjectivesTo compare comorbidities in a cohort of cyclic citrullinated peptide (CCP) antibody positive patients without or prior to onset of inflammatory arthritis (IA) to those in patients with early IA.MethodsBaseline data from two established cohorts were used. The first recruited people at risk of IA: CCP antibody positive cases without IA (CCP Cohort, n = 296). The second cohort [the Inflammatory Arthritis CONtinuum study (IACON)] recruited patients with early IA (n = 725). Proportions of patients with gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Moreover, ACPA is associated with a more aggressive RA course and with EMs [24]. A recent study by Twigg et al on more than a thousand RA patients demonstrated that the comorbidities in ACPA-positive patients without inflammatory arthritis are the same as patients with early inflammatory arthritis [25]. This suggests that comorbidities in ACPA-positive patients may begin to appear before the onset of clinical signs of inflammation.…”
Section: Cardiovascular Disease and Chronic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ACPA is associated with a more aggressive RA course and with EMs [24]. A recent study by Twigg et al on more than a thousand RA patients demonstrated that the comorbidities in ACPA-positive patients without inflammatory arthritis are the same as patients with early inflammatory arthritis [25]. This suggests that comorbidities in ACPA-positive patients may begin to appear before the onset of clinical signs of inflammation.…”
Section: Cardiovascular Disease and Chronic Inflammationmentioning
confidence: 99%
“…This suggests that comorbidities in ACPA-positive patients may begin to appear before the onset of clinical signs of inflammation. In particular, ACPA positivity contributes to the development of CVD [25] and may induce subclinical atherosclerotic damage [26].…”
Section: Cardiovascular Disease and Chronic Inflammationmentioning
confidence: 99%
“…Ранее было доказано, что антитела к циклическому цитруллинированному пептиду (АЦЦП) связаны с более высокой частотой внесуставных проявлений и худшими исходами, а также с патогенезом сердечнососудистой недостаточности [2,3] и развитием диастолической дисфункции левого желудочка (ДДЛЖ) [5,8] при РА. Наряду с этим было отмечено, что желудочковая дисфункция связана с более длительной продолжительностью заболевания и повышенными серологическими маркерами ревматоидного артрита [4].…”
Section: Abstract: Rheumatoid Arthritis Antibodies To Cyclic Citrullunclassified